Analisis Determinan Pertumbuhan Sektor Pertanian di Provinsi Sumatera Utara - Aulya Maharany; Malika Hasnadia; Sherly Alya Kanesya; Dewi Rohma Wati (Sharia Agribusiness Journal, 2026)
This study aims to analyze the contribution of labor, government expenditure, Domestic Investment (PMDN), and Foreign Investment (PMA) in supporting the development of the agricultural sector in North Sumatra Province. This research uses secondary data obtained from the Central Bureau of Statistics (BPS), including data on agricultural labor, regional government expenditure, Domestic Investment (PMDN), Foreign Investment (PMA), and Gross Regional Domestic Product (GRDP) of the agricultural sector in North Sumatra Province during the period 2014–2024. The analytical method used in this study is multiple linear regression with the Ordinary Least Square (OLS) approach to determine the effect of each independent variable on the dependent variable, namely the GRDP of the agricultural sector. The results show that labor has a positive and significant effect on the GRDP of the agricultural sector in North Sumatra Province, indicating that an increase in the number of workers can encourage production capacity and sustainable growth in the agricultural sector. Meanwhile, government expenditure, Domestic Investment (PMDN), and Foreign Investment (PMA) do not show a significant effect on the GRDP of the agricultural sector during the study period. The negative coefficients of government expenditure and PMDN indicate that government budget allocation and domestic investment have not been utilized optimally for productive activities that can directly increase agricultural output in the short term. In addition, the insignificant effect of PMA indicates that foreign investment in North Sumatra Province tends to be directed more toward non-agricultural sectors, so its contribution to the agricultural sector remains relatively limited. Based on these findings, efforts are needed to improve the quality and productivity of labor through training and skill development, increase the effectiveness of government spending, especially capital expenditure oriented toward agricultural infrastructure development, and manage domestic and foreign investment more effectively so that it can provide a greater impact on the growth of the agricultural sector in North Sumatra Province. Therefore, the results of this study are expected to serve as a reference in formulating agricultural development policies in North Sumatra Province.